(N-Benzyl-N-isopropyldithiocarbamato)chloridodiphenyltin(IV) - Muthalib, A.F.A.; Baba, I.; Tahir, M.I.M.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The Sn(IV) atom in the title organotin dithiocarbamate, [Sn(C(6)H(5))(2)(C(11)H(14)NS(2))Cl], is penta-coordinated by an asymmetrically coordinating dithiocarbamate ligand, a Cl and two ispo-C atoms of the Sn-bound phenyl groups. The resulting C(2)ClS(2) donor set defines a coordination geometry intermediate between square-pyramidal and trigonal-bipyramidal with a slight tendency towards the latter. The formation of close intramolecular C-H center dot center dot center dot Cl and C-H center dot center dot center dot S contacts precludes the Cl and S atoms from forming significant intermolecular contacts. The presence of C-H center dot center dot center dot pi contacts leads to the formation of supramolecular arrays that stack along the b axis.